2011
DOI: 10.1007/s00330-011-2177-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and further differentiation of subendocardial and transmural myocardial infarction by fast strain-encoded (SENC) magnetic resonance imaging at 3.0 Tesla

Abstract: Objectives: To investigate whether subendocardial and transmural myocardial infarction can be identified and differentiated using the peak circumferential and longitudinal strains measured by fast strain-encoding (SENC).Methods: Nineteen patients with ischemic heart diseases underwent imaging with fast SENC and late gadolinium enhancement (LGE) MRI at 3T. Fast SENC measurements were performed in three short-axis slices (basal, mid-ventricular and apical levels) and one long-axis view (four-chamber) to assess p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…Another echocardiographic study also demonstrated the noninferiority of circumferential strain compared to LGE for the prediction of global functional recovery, which is in close agreement to our findings [35]. In the same line, a recent CMR study showed that circumferential strain has higher sensitivity and specificity for the differentiation of subendocardial versus transmural myocardial infarction, compared to longitudinal strain [36]. Although the prognostic value of circumferential compared to that of longitudinal strain is rated differently in the current literature [37,38], it seems that such differential effects between subendocardial and transmural infarctions on longitudinal and circumferential strains may be a consequence of the helical wrapping of cardiac fibers into three different anatomical layers, as described in previous experimental studies [39].…”
Section: Earlier Studies Using Ultrasound and Cmr Based Deformationsupporting
confidence: 92%
“…Another echocardiographic study also demonstrated the noninferiority of circumferential strain compared to LGE for the prediction of global functional recovery, which is in close agreement to our findings [35]. In the same line, a recent CMR study showed that circumferential strain has higher sensitivity and specificity for the differentiation of subendocardial versus transmural myocardial infarction, compared to longitudinal strain [36]. Although the prognostic value of circumferential compared to that of longitudinal strain is rated differently in the current literature [37,38], it seems that such differential effects between subendocardial and transmural infarctions on longitudinal and circumferential strains may be a consequence of the helical wrapping of cardiac fibers into three different anatomical layers, as described in previous experimental studies [39].…”
Section: Earlier Studies Using Ultrasound and Cmr Based Deformationsupporting
confidence: 92%
“…60 Peak systolic E CC and E LL at real-time fast SENC has shown usefulness in identifying chronic myocardial infarctions and determining the myocardial scar transmurality. 61 Few studies have been performed to date assessing the clinical utility of FT-CMR in patients with IHD. FT-CMR applied to patients enrolled in the Amoricyte Phase I trial evaluating the influence of stem cell therapy infused into an infarct-related artery 5 to 11 days after primary coronary intervention demonstrated modest improvement in peak segmental E CC in a comparison with control subjects, suggesting the feasibility of this technique.…”
Section: Key Pointsmentioning
confidence: 99%
“…In contrast, the pixel-based evaluation with SENC was useful for diŠerentiating subendocardial and transmural myocardial infarctions. 7 The Compared to SENC, the SPAMM method is limited by tag space and its segment-based analysis. DiŠerences between the 2 methods might be due to the limitations of the SPAMM method.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded 40 patients with late gadolinium enhancement (LGE) because of the inhomogeneous nature of the myocardium. 7 We used a diŠerent analysis software package for each method. We focused on diŠerences in the 2 diŠerent methods without errors due to regional inhomogeneity.…”
Section: Methodsmentioning
confidence: 99%